Detour from the Poverty Reduction Path : Uganda Poverty Update Note - Uganda National Household Survey 2016-17 - World Bank (World Bank, Washington, DC, 2021)
Uganda’s progress in reducing poverty during the late 1990s and early 2000s was remarkable. This note documents the trends in poverty and inequality in Uganda with a focus on the period 2012 to 2016. It first explores how various indicators of monetary poverty have evolved over time and if these trends vary by urban and rural areas and by region. This is complemented with a description of the movements in several non-monetary poverty indicators. Secondly, the note analyzes who has benefitted from the lackluster economic growth, and how this has translated into different measures of inequality. It then aims to disentangle some of the forces behind the changes in poverty, mostly resorting to decomposition exercises. Finally, it provides an account of who are the poor households and what are their living conditions, particularly compared to non-poor households.